Considerações sôbre o ensino atual da matemática - D'Ambrosio, Ubiratan (2010)
This paper raises the need for change in Mathematics programs that take into account the current state of science and research about what, when, to whom and why to teach Mathematics. This requires the incorporation of  mathematicians, teachers, researchers, technicians and psychologists.It is suggested that the curriculum gradually promote abstraction, includ ngformative and informative values, emphasizing the former, and provides practical ideas about the development of content across years of Secondary Education.